Language ideologies and pedagogical tensions: Norwegian teachers’ and students’ attitudes toward home language use in the EAL classroom - Neokleous, Georgios; Natlandsmyr, Kristina Vangen (Frontiers in Education, 2025)
IntroductionThis study explores the attitudes of students and teachers toward home language (HL) integration in English as an Additional Language (EAL) classrooms in Norway. As multilingualism becomes increasingly visible in Norwegian schools, the traditional emphasis on monolingual, target-language (TL)-only instruction is being questioned.MethodsDrawing on data from classroom observations and semi-structured interviews with six EAL teachers and 32 students across three linguistically diverse lower secondary schools, this study examines how HL use is perceived, enacted, and negotiated in practice.ResultsThe findings highlight two central themes. First, both students and teachers demonstrated a strong ideological commitment to English as the primary language of instruction. Teachers frequently positioned themselves as gatekeepers of TL exposure, citing institutional expectations and professional norms that prioritize English-only approaches. Similarly, students—especially in the upper grades—viewed TL immersion as essential preparation for exams and future opportunities. However, classroom practices often deviated from these ideological positions. Teachers routinely used HLs, particularly Norwegian, for clarification, translation, and classroom management, especially in mixed-ability settings. Students also identified HL use as helpful for reducing stress, boosting comprehension, and making abstract concepts more accessible. While English remained the main instructional language, HLs were valued as supportive tools rather than threats to learning. The second theme concerns the constraints and uncertainties limiting systematic multilingual implementation. Teachers reported feeling underprepared and unsupported when drawing on students’ broader linguistic repertoires. While many recognized the benefits of HL integration, they voiced concerns about time, fairness, and feasibility, particularly when students’ HLs differed from their own. Students, too, expressed mixed feelings: while many supported HL use, some worried it might highlight linguistic differences or create divisions.DiscussionOverall, the study suggests that HL integration is not a binary choice but a dynamic, context-dependent negotiation. The findings underscore the need for clearer policy frameworks, targeted teacher training, and classroom-based examples to support inclusive language teaching. By foregrounding the voices of both teachers and learners, the study contributes to ongoing discussions on how multilingualism can be meaningfully integrated into EAL pedagogy in Norway and similar contexts.